Perbaikan Waktu Set Up Antar Batch Pada Proses Pencetakan Obat Sediaan Solid di PT. Kalbe Farma Tbk Dengan Metode SMED - Raharja, Reza Agustian; Naro, Aulia (Universitas Mercu Buana, 2020)
PT KALBE FARMA TBK is one of the largest pharmaceutical companies in Indonesia. The obstacle faced by the company is the waste of set up time in the area of the drug printing process, especially solid preparations. This study aims to reduce the set up time between batches by using the SMED method. The method used in data collection is by direct observation in the field. The data processing method is carried out by conducting data adequacy test and data uniformity test, then calculating the average time for the set up time between batches. The research shows that when setting up between batches there are 12 activities that must be done by the operator with an average set up time of 106.00 minutes. After implementing SMED and Improvement, it can be minimized to 7 activities with a total set-up time of 51.75 minutes on average. So that there was a decrease in the set up time of 54.25 minutes.